AVONET: morphological, ecological and geographical data for all birds - Tobias, Joseph A.; Sheard, Catherine; Pigot, Alex L.; Devenish, Adam J.M.; Jingyi Yang; Sayol, Ferran; Neate‐Clegg, Montague H.C.; Alioravainen, Nico; Weeks, Thomas L.; Barber, Robert A.; Walkden, Patrick A.; MacGregor, Hannah E.A.; et al. (Wiley, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species-level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.